The CFTR Met 470 allele is associated with lower birth rates in fertile men from a population isolate. - Gülüm Kosova; Joseph K Pickrell; Joanna L Kelley; Patrick F McArdle; Alan R Shuldiner; Mark Abney; Carole Ober (PLoS Genetics)
Although little is known about the role of the cystic fibrosis transmembrane regulator (CFTR) gene in reproductive physiology, numerous variants in this gene have been implicated in etiology of male infertility due to congenital bilateral absence of the vas deferens (CBAVD). Here, we studied the fertility effects of three CBAVD-associated CFTR polymorphisms, the (TG)m and polyT repeat polymorphisms in intron 8 and Met470Val in exon 10, in healthy men of European descent. Homozygosity for the Met470 allele was associated with lower birth rates, defined as the number of births per year of marriage (P = 0.0029). The Met470Val locus explained 4.36% of the phenotypic variance in birth rate, and men homozygous for the Met470 allele had 0.56 fewer children on average compared to Val470 carrier men. The derived Val470 allele occurs at high frequencies in non-African populations (allele frequency = 0.51 in HapMap CEU), whereas it is very rare in African population (Fst = 0.43 between HapMap CEU and YRI). In addition, haplotypes bearing Val470 show a lack of genetic diversity and are thus longer than haplotypes bearing Met470 (measured by an integrated haplotype score [iHS] of -1.93 in HapMap CEU). The fraction of SNPs in the HapMap Phase2 data set with more extreme Fst and iHS measures is 0.003, consistent with a selective sweep outside of Africa. The fertility advantage conferred by Val470 relative to Met470 may provide a selective mechanism for these population genetic observations.